2019
DOI: 10.1177/1065912919861154
|View full text |Cite
|
Sign up to set email alerts
|

Human Rights Abused? Terrorist Labeling and Individual Reactions to Call to Action

Abstract: What leads individuals to be motivated to act for human rights causes? Human rights organizations (HROs) often use personal and emotional stories of the abused in order to gain the attention of individuals reading newspapers or emails directly from the organization. McEntire, Leiby, and Krain show that personal frames are most successful at increasing knowledge about a specific human rights situation and motivating individuals to act. However, HROs are not operating in a political vacuum; repressive government… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The authors show that personalist frames are the most effective at garnering opposition to sleep deprivation torture techniques. Adding nuance to these findings, Bracic and Murdie (2020) also show that personalist campaigns are effective, but that respondents are less receptive to these efforts when the government has labeled the victim of human rights abuse a terrorist. Haines et al (2020) find that personalist campaigns can increase sympathy for victims while also increasing support for retributive violence.…”
Section: Transnational Advocacy and Public Opinionmentioning
confidence: 83%
“…The authors show that personalist frames are the most effective at garnering opposition to sleep deprivation torture techniques. Adding nuance to these findings, Bracic and Murdie (2020) also show that personalist campaigns are effective, but that respondents are less receptive to these efforts when the government has labeled the victim of human rights abuse a terrorist. Haines et al (2020) find that personalist campaigns can increase sympathy for victims while also increasing support for retributive violence.…”
Section: Transnational Advocacy and Public Opinionmentioning
confidence: 83%
“…Indeed, our respondents display strong support for human rights, while the support for climate action is more divided ( Supplementary Material figures A5 and A6 ). Another reason might be that human rights violations evoke stronger emotional reactions than noncompliance in other areas of global governance ( Bracic and Murdie 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, human rights principles are often framed as detrimental to security. A recent study found that individuals are less likely to be mobilized for human rights if the individual tortured is labeled a terrorist (Bracic and Murdie 2020). Similarly, support for free speech may diminish if there is an external threat (Dietrich and Crabtree 2019).…”
Section: Human Rights As Public Opinion-related Policy Choicementioning
confidence: 99%